2021
DOI: 10.1038/s41598-021-87498-z
|View full text |Cite
|
Sign up to set email alerts
|

Flow-diverting devices in the treatment of unruptured ophthalmic segment aneurysms at a mean clinical follow-up of 5 years

Abstract: A shift toward the endovascular treatment of ophthalmic segment aneurysms is noticeable. However, it is not clear if the long-term treatment results improve with the development of endovascular methods. The aim of this study was to present the outcomes of the treatment of unruptured ophthalmic aneurysms using flow diverting devices (FDD) with or without coiling. This retrospective study included 52 patients with 65 UIAs treated in 2009–2016. The mean aneurysm size was 8.8 mm. Eight aneurysms were symptomatic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Literature search was performed on March 21, 2022. After removal of duplicates and screening of titles and abstracts, we sought for the original articles of 82 publications 7 13–93. After completion of literature review and data extraction and before closing the database, the literature search was repeated on PubMed only on May 22, 2022, using the above-mentioned search string to identify additional potentially eligible articles.…”
Section: Resultsmentioning
confidence: 99%
“…Literature search was performed on March 21, 2022. After removal of duplicates and screening of titles and abstracts, we sought for the original articles of 82 publications 7 13–93. After completion of literature review and data extraction and before closing the database, the literature search was repeated on PubMed only on May 22, 2022, using the above-mentioned search string to identify additional potentially eligible articles.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 With the development of novel devices and the need for less invasive treatment, an increasing number of paraclinoid aneurysms are referred for endovascular treatment. [4][5][6][7][8][9][10][11] Flow diversion has been a promising treatment strategy for paraclinoid aneurysms in the quest for a more effective treatment aiming for stable aneurysmal exclusion, but the technique of stents in embolization of wide-necked paraclinoid aneurysms is still used in treating routine aneurysms. 8,[10][11][12][13][14][15][16] Previous studies have reported that the dorsally located aneurysms may increase the technical difficulty of endovascular embolization due to the unfavorable aneurysmal geometries and the severe curvature of the carotid siphon.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Flow diversion has been a promising treatment strategy for paraclinoid aneurysms in the quest for a more effective treatment aiming for stable aneurysmal exclusion, but the technique of stents in embolization of wide-necked paraclinoid aneurysms is still used in treating routine aneurysms. 8,[10][11][12][13][14][15][16] Previous studies have reported that the dorsally located aneurysms may increase the technical difficulty of endovascular embolization due to the unfavorable aneurysmal geometries and the severe curvature of the carotid siphon. 17,18 However, the comparative data of characteristics and treatment results with stent application in different projections of paraclinoid aneurysms are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several treatment options have been described for these aneurysms, including microsurgical clipping, flow diversion, and coil embolization, each with advantages and disadvantages. [3][4][5][6][7][8][9] The "Dallas Technique" was described originally in 1990 4 and is currently used less frequently, as endovascular techniques have gained preeminence; yet, its utility remains very high, and we believe it is important for the younger cerebrovascular microsurgeon to remain familiar with it. We present the case of a 71-year-old woman who presented with worsening headaches, visual acuity 20/20, and visual fields full to confrontation bilaterally.…”
mentioning
confidence: 99%